Structural and Potential Functional Properties of Alkali-Extracted Dietary Fiber From Antrodia camphorata - Yongjun Xia; Peng Meng; Shaodong Liu; Zhuoming Tan; Xi Yang; Lihong Liang; Fan Xie; Hui Zhang; Guangqiang Wang; Zhiqiang Xiong; Jenyu Lo; Lianzhong Ai (Frontiers in Microbiology, 2022)
Antrodia camphorata is rich in a variety of bioactive ingredients; however, the utilization efficiency of the residue of A. camphorata is low, resulting in serious waste. It is necessary to deeply study the functional components of A. camphorata residues to achieve high-value utilization. In this study, the components, structural characteristics, and functional properties of alkali-extracted dietary fiber extracted from residues of A. camphorata (basswood and dish cultured fruiting body, respectively) were investigated. There were similar components and structural characteristics of ACA-DK (extract from basswood cultured) and ACA-DF (extract from dish cultured). The two alkali-extracted dietary fiber were composed of mainly cellulose and xylan. However, ACA-DK has better adsorption capacities than ACA-DF on lipophilic substances such as oil (12.09 g/g), cholesterol (20.99 mg/g), and bile salts (69.68 mg/g). In vitro immunomodulatory assays stated that ACA-DK had a good effect on promoting the proliferation of RAW 264.7 cells and can activate cell phagocytosis, NO synthesis, and other immune capabilities. The edible fungus A. camphorata is a good source of functional dietary fiber. The alkali-extracted dietary fiber of A. camphorata might be used as a functional ingredient in the medicine and food industry.